ASSESSMENT OF THE RELATIONSHIP BETWEEN SERUM TWEAK LEVELS AND THE DEGREE OF VASCULAR INVOLVEMENT IN PATIENTS WITH STABLE ANGINA PECTORIS - Şirikçi, Vehbi; Fındıklı, Hüseyin Avni; Öztürk, Savaş (Sanamed, 2024)
Introduction: This study investigates the relationship between serum TWEAK levels and the degree of vascular involvement in patients with stable angina pectoris, offering insights beyond conventional cardiovascular risk factors.Materials and Methods: This study involved 88 patients (33 women, 55 men) diagnosed with stable angina pectoris. Patients were classified based on angiographic findings. Comprehensive demographic and medical history data were collected, and morning blood samples were analyzed, focusing on TWEAK and IL-6 levels. To assess the severity of coronary artery lesions, a modified version of the Gensini scoring system was employed.Results: Analyses revealed no significant correlation between TWEAK levels and the severity of coronary artery disease. Although some variations in biochemical markers were observed based on gender and diabetic status, these differences did not exhibit a statistically significant relationship with the degree of vascular involvement.Conclusion: The findings indicate that serum TWEAK levels do not have a significant association with the severity of vascular involvement in patients with stable angina pectoris. These results highlight the limited efficacy of TWEAK as a sole biomarker in assessing the severity of coronary artery disease, emphasizing the complexity of its role.
Keywords: Tweak; Angina pectoris; Gensini score